Inheritance Distribution System: A One-To-Two Analysis of The Axological Perspective of Islamic Law Philosophy - Asman, Asman; Kolyazhor, Andrey V. (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
This study discusses the division of inheritance one to two in Indonesia which is reviewed from the philosophy of Islamic law. In the philosophy of Islamic law, every discussion of Islamic law is inseparable from the study of axiology, epistimology and ontology. The division of inheritance in Indonesia is experiencing controversy between women and men in gender issues. The Qur'an surah an-nisa verse 11 explains that the distribution of inheritance has been determined, but in fact in Indonesian society, especially the Muslami people, in the distribution of inheritance between daughters and sons, there are those who use the concept of one to one. Is the division of inheritance one to one contrary to the Qur'an which is Islamic Shari'a. The focus in this study is how the axiology of the one-to-two dimension in the division of inheritance in Indonesia perspectives of Islamic legal philosophy. The method in this study is a qualitative research method that is bibliographical. This study took data through references or references from books, journals, mass media and other references relevant to this study. Meanwhile, the findings in this study are that from the axiological perspective of Islamic legal philosophy, the division of inheritance is one to two, reflecting the value of substantive justice, not formal justice. This substantive justice seeks to balance the rights and obligations between men and women in accordance with their respective social roles and responsibilities in society. [Penelitian ini membahas terkait pembagian waris satu banding dua di Indonesia yang di tinjau dari filsafat hukum islam. Dalam filsafat hukum islam menjalaskan setiap pembahasan hukum islam tidak terlepas dari kajian aksiologi, epistimologi dan ontologi. Pembagian waris di indonesia mengalami kontroversi antara perempuan dan laki-laki masuk dalam isu gender. Al-Qur’an surat an-nisa ayat 11 menjelaskan dalam pembagian waris sudah ditentukan bagiannya, tetapi kenyataannya di masyarakat indonesia khususnya umat muslami dalam pembagian waris antara anak perempuan dan anak laki-laki ada yang menggunakan konsep satu banding satu. Apakah pembagian waris satu banding satu bertentangan dengan al-Qur’an yang merupakan syariat islam. Fokus dalam penelitian ini adalah bagaimana aksiologi dimensi satu banding dua dalam pembagian waris di Indonesia prespektif filsafat hukum islam. Metode dalam penelitian ini adalah metodoe penelitian kualitatif yang bersifat kepustakaan. Penelitian ini mengambil data melalui rujukan atau referensi dari buku, jurnal, media masa dan referensi lainnya yang relevan dengan penelitian ini. Sementara itu, temuan dalam penelitian ini adalah Dari perspektif aksiologis filsafat hukum Islam, pembagian warisan adalah satu banding dua mencerminkan nilai keadilan substantif, bukan keadilan formal. Keadilan substantif ini berupaya menyeimbangkan hak dan kewajiban antara laki-laki dan perempuan sesuai dengan peran dan tanggung jawab sosial masing-masing dalam masyarakat].